2016
DOI: 10.1016/j.nmni.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of NDM-1 and OXA-72 producing Acinetobacter pittii clinical isolates in Lebanon

Abstract: Acinetobacter spp. have emerged as global opportunistic pathogen causing a wide range of infections. Emergence of carbapenem resistance in these organisms is a matter of great concern. We report here the first detection of Acinetobacter pittii clinical isolates in Lebanon carrying either the blaNDM-1 or the blaOXA-72 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…As for non-A. baumannii strains, a single study reported the first detection of A. pittii harboring the blaNDM-1 or the blaOXA-72 gene from a hospital located in the north of Lebanon [23]. This study highlights the importance of non baumannii strains in the clinical settings as suggested by other worldwide studies.…”
Section: Epidemiology Of Carbapenem Resistant Acinetobacter Species Isupporting
confidence: 58%
See 1 more Smart Citation
“…As for non-A. baumannii strains, a single study reported the first detection of A. pittii harboring the blaNDM-1 or the blaOXA-72 gene from a hospital located in the north of Lebanon [23]. This study highlights the importance of non baumannii strains in the clinical settings as suggested by other worldwide studies.…”
Section: Epidemiology Of Carbapenem Resistant Acinetobacter Species Isupporting
confidence: 58%
“…Kanj et al associated Acinetobacter anitratus bacteremia to an early relapse of thrombotic thrombocytopenic purpura in a 58 years old male during plasma exchange therapy in 2003 [22]. On the other hand, A. pittii was detected in the urine culture of a four-month-old child as well as from febrile gastroenteritis infected patient [23].…”
Section: Acinetobacter Baumannii In Lebanon: a Real Threat Or An Overmentioning
confidence: 99%
“…Moreover, the first description of a bla OXA-143-like strain is reported here, which was isolated in 2014 from a wound sample of a female patient admitted to TGH. Alarmingly, since the first description in Lebanon of a bla NDM-1 -positive A. baumannii 30 and Acinetobacter pittii, 31 four more isolates were found in this study.…”
Section: Discussionmentioning
confidence: 61%
“…In Lebanon, the bla OXA-72 was firstly described in A. calcoaceticus isolated from purchased vegetables in Beirut [28]. It is also found in A. pittii isolated from patients admitted to Lebanese hospital in North of Lebanon, in 2015 [29]. Moreover, Rafei et al reported that among 31 carbapenem-resistant strains collected from different hospitals in Beirut and Northern Lebanon, 28 isolates carried the bla OXA-23 gene, 1 strain the bla OXA-24 gene and 2 strains the bla OXA-58 gene [30].…”
Section: Discussionmentioning
confidence: 99%